Calm before the Storm in the European Tourism Sector: Pre-COVID-19 Multivariate Competitive Position Analysis in the 2011-2019 Period - ŚLEDZIK, Karol; PŁOSKA, Renata; CHMIELEWSKI, Mariusz; BAREMBRUCH, Adam (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.v12.6(54).23, 2021)
The impact of tourism on GDP results, inter alia, from the creation of various jobs in the widely understood tourism sector, as well as from travels made both by citizens within their country and by foreigners. Such travels entail expenditure on various goods and services. The coronavirus pandemic that broke out in 2020 caused significant losses in the economic area in all European Union (EU) countries. The restrictions implemented in connection with the pandemic affected the tourism sector the most. The aim of this paper is an assessment of the competitive position of EU27 countries from the tourism sector perspective. The study is based on the analysis of the competitive position of the tourism sector in EU member countries in the pre-COVID era, which is why the research period was 2011-2019. The tool for achieving this objective was a multivariate comparative analysis. The position can be assessed on the basis of various sub-measures, but this does not give a complete picture, only a fragmented one. Our goal was to show the picture holistically - proposing the SMD methodology. The conclusions of the study show that there is differentiation that persists over the long research period. The positions of individual countries are maintained. The same countries occupy both top and bottom positions. COVID-19 is a new factor, not included in the analysis, which may affect the results of such analyses in the future, both in short- and long-term perspective. In this context, our results can provide a starting point and a benchmark for assessing these developments in the coming years.